Reports of bottlenose dolphin deaths in the Wildlife Refuge Lanzanillo-Pajonal-Fragoso, Cuba/ Reportes de muertes de delfines mulares en el Refugio de Vida Silvestre Lanzanillo- Pajonal-Fragoso, Cuba - Julio Rodríguez-González (Revista de Investigaciones Marinas, 2018)
Dolphins are among the most charismatic and peculiar organisms that inhabit marine-coastal ecosystems. Their populations have been affected in recent decades by commercial exploitation, nature tourism, poaching and the use of nonspecific fishing gear with the subsequent bycatch; being the last two, causing multiple deaths in the natural populations of these organisms. The objective of this study is to alert the scientific community and resident populations about the behavior of deaths and stranding of dolphins Tursiops truncatus in locations of the Lanzanillo-Pajonal-Fragoso Wildlife Refuge, Cuba. Cadaver samples were collected between years 2005- 2017. The dead bodies were classified according to the decomposi- tion period in fresh, decomposed, or dry bones. Data were collected about the probable cause of death and the location of the stranding. The year with the highest number of dead bodies found (four) was 2007, followed by the years 2005 and 2014, each with three bodies. The locality that reported the highest number of dead bodies was Bahía de Nazabal (eight), in accordance with the high productivity and fishing effort that it presents. A total of 15 dead bodies were found in the studied period, of these it was determined that five individuals were slaughtered for consumption, eight were acciden- tally entanglement in fishing nets and for two specimens it was not possible to determine the cause of death. The results obtained in this work contribute directly to the management and conservation of the natural populations of dolphins, as well as to the implemen- tation of programs that involve the community.